he degree of availability of some basic science process skills in the content of the science textbook for the fourth grade - العكاش , رياض; رغداء نصور; منار العدي (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The current study aims to reveal the degree of availability of some basic science process skills in the content of the science textbook for the fourth grade, in the Syrian Arab Republic. To achieve this goal, the researcher adopted the descriptive approach and prepared a list of the basic science processes that consisted of three science processes (inference, observation, and classification). On its basis, the analysis tool represented by the analysis form was designed in order to analyze the study sample consisting of the science book for the fourth grade, and the researcher verified the validity and reliability of the analysis according to it. The results of the research showed the availability of the three science processes in the science book for the fourth grade, but they were mentioned in varying proportions; Inferential processes ranked first with 88 frequencies and a percentage of 57.9%, observation ranked second with 46 frequencies and a percentage of 30.26%, and classification ranked third with 18 frequencies and a percentage of 11.84%, and based on that, the researcher presented suggestions..